2016
DOI: 10.1097/qai.0000000000000986
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Kidney Function and in the Rate of Tubular Dysfunction After Tenofovir Withdrawal or Continuation in HIV-Infected Patients

Abstract: Our data support the role of use and time on TDF in eGFR decline and tubular dysfunction. In contrast, TDF withdrawal is followed by a rapid and significant, although partial, recovery of eGFR and tubular abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 29 publications
2
31
1
2
Order By: Relevance
“…Previously, there have been a few case reports describing the reversal of ADV and TDF-related Fanconi's syndrome after TDF withdrawal in patients with CHB [12,26]. In contrast, our study showed that nucleotide analogue-related PRTD could be resolved in 16 CHB patients after discontinuation of nucleotide analogue similar to the phenomenon that occurs in HIV-infected patients [21][22][23][24][25]. The complete reversal of nucleotide analogue PRTD occurred in 81% of the patients at one year.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Previously, there have been a few case reports describing the reversal of ADV and TDF-related Fanconi's syndrome after TDF withdrawal in patients with CHB [12,26]. In contrast, our study showed that nucleotide analogue-related PRTD could be resolved in 16 CHB patients after discontinuation of nucleotide analogue similar to the phenomenon that occurs in HIV-infected patients [21][22][23][24][25]. The complete reversal of nucleotide analogue PRTD occurred in 81% of the patients at one year.…”
Section: Discussioncontrasting
confidence: 45%
“…In contrast to these studies [4][5][6]17], PRTD and impaired phosphate renal tubular reabsorption were seen in 15-48% of CHB patients receiving long-term ADV and TDF therapy as in real world clinical experience [8,10,[18][19][20]. Reversibility of renal dysfunction has been shown in HIV-infected patients after cessation of TDF [21][22][23][24][25]. A few cases of reversible TDF or ADV-induced PRTD and Fanconi's syndrome have been reported in CHB patients after stopping treatment with nucleotide analogues [12,26].…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Older age or a lower baseline creatinine clearance (≤90ml/min) at the initiation of PrEP were each independently associated with a faster rate of renal decline or a risk of CrCl falling ≤60ml/min or ≤70ml/min, especially with daily dosing, so more intensive safety monitoring in patients with these baseline characteristics may be indicated. Other treatment settings have shown similar risk factors (age and marginal renal function) for TDF-associated toxicity 814 and two other PrEP studies have shown that older age predicts greater declines in renal function on PrEP. 5,6 …”
Section: Discussionmentioning
confidence: 81%
“…With TDF/FTC-based treatment, greater declines in renal function are associated with longer duration of TDF use 811 , as well as older age 8,12,13 or lower baseline renal function 11,14 at TDF initiation. In the placebo-controlled efficacy trials of PrEP, baseline renal function was required to be within normal range prior to randomization, and trial participants were generally young.…”
Section: Introductionmentioning
confidence: 99%